1959
DOI: 10.1149/1.2427332
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Electrochemical Characteristics of Organic Compounds

Abstract: A theory based on the electron density in the vicinity of a reducible nitro group which had been used to explain the effect of substituent groups and their position on the operating potential of aromatic nitro compounds has been extended to the nitroalkane compounds. The high theoretical ampere-minute capacity of the nitroalkane compounds, along with their high operating potentials, show these compounds to have considerable promise for use as cathode materials in primary cells.) unless CC License in place (see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1960
1960
1997
1997

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
(12 reference statements)
0
9
0
Order By: Relevance
“…c. Electrochemical Reduction The electrochemical characteristics of several polynitro compounds have been determined by Glicksman and Morehouse (61). With the data obtained, they have extended to nitroalkanes the theory which had been used to explain the effect of substituent groups and their positions on the operating potential of aromatic nitro compounds.…”
Section: Reduction Of Polynitro Compoundsmentioning
confidence: 99%
“…c. Electrochemical Reduction The electrochemical characteristics of several polynitro compounds have been determined by Glicksman and Morehouse (61). With the data obtained, they have extended to nitroalkanes the theory which had been used to explain the effect of substituent groups and their positions on the operating potential of aromatic nitro compounds.…”
Section: Reduction Of Polynitro Compoundsmentioning
confidence: 99%
“…Electrocatalytic investigations of nitrobenzene reduction on platinum and platinum-ruthenium cathodes in acidic electrolytes showed that reaction proceeded through a mixed mechanism, involving electron transfer and surface reaction (87, 106). Studies with substituted nitro compounds indicate that the cathode potential depended on the type and position of the substituents (47). Similar behavior is exhibited by quiñones (46).…”
Section: Electrogenerative Reduction Of Nitro Compoundsmentioning
confidence: 68%
“…References to the hundreds of succeeding studies on nitro-reduction are available from the review on cathode reduction and standard compilations (1,111). The possible use of polynitrobenzenes as battery depolarizers has motivated still further study (3,46,47,52,53,62,87,113,116). However, many of these studies have taken place at potentially catalytically poisoning mercury electrodes.…”
Section: Electrogenerative Reduction Of Nitro Compoundsmentioning
confidence: 99%
“…Most perfluoroalkylamines, by virtue of their chemical inertness and thermal stability, have been suggested for use as hydraulic fluids, lubricants, and solvents. Trichloronitromethane may be used as a cathode in dry batteries (141). The polymerization of perfiuoroolefins is catalyzed by hexafluorodimethyl disulfide (57) as well as by bis(trifluoromethylthio)mercury (57,102).…”
Section: Uses Of N- O- and S-trihalomethyl Compoundsmentioning
confidence: 99%